ANALISIS EFISIENSI DAN PRODUKTIVITAS TENAGA KERJA INDUSTRI TEPUNG TERIGU DI INDONESIA PERIODE 1997-2008 - Yohana Rain Elisabet (Jurnal Ekonomi Pembangunan, 2012)
This research aimed to (1) explain how development the efficiency of wheat flour industry in Indonesia (2) explain how development the labour of productivity of wheat flour industry in Indonesia. The data that used in this research was secondary data, namely value added, input costs, value of gross output, intermediate costs and number of workers in period 1997-2008. The basic theory used are the theory of efficiency and labour of productivity. Funding analysis, this research show that the efficiency of wheat flour industry inclined is not yet efficiency. Meanwhile labour of productivity to increase every year. Keywords: Efficiency and Labour of Productivity